NUMERICAL MODELING OF CHARACTERISTICS AND PARAMETERS OF A NOISE RADAR SENSOR FOR EARTH’S SURFACE MAPPING - V. E. Kudryashov; K. A. Lukin; D. N. Tatyanko (Radio Physics and Radio Astronomy)
Subject and Purpose. The work presents numerical modeling results on the characteristics and parameters of a Noise Radar Sensor (NRS) during remote sensing of terrestrial surfaces. The radiometric (passive) mode and the mode with "backlighting" (active) of the mapping scene are considered. Radiometric signals of surfaces at wavelengths of 3.37 and 1.34 mm are used along with echo signals from the same surfaces under their backlighting (or illuminating) with ultra-weak-power quasicontinuous noise-like signals at a wavelength of 1.53 mm. The focus is on developing a numerical modeling technique to calculate the potential input characteristics of the NRS and compare them with the output parameters of the imagery.